Dark matter, deep space frequencies and new era of space communication - Biswas, Pallab (International Journal of Advanced Astronomy, 2023)
Dark matter is the cosmological link that stayed universe to multiuniverse. All universal parameters directly or indirectly show that the dark matter is the universe hidden energy or soul. We have no confusion about the existence of Dark matter. As it is the universe linker we can make a communication through it. May be higher intelligence out of universe( Alien) are working on it as every time we are receiving unidentified signal from outer space. Previous paper had shown that how the dark matter is established and expanded on the universe. This paper is showing about deep space frequencies, energy distribution with quantum fluctuation and dark matter communication. And at last is discussed for making a quantum mechanical signal for long distance like galaxy to galaxy communication. By dark matter communication we can make stronger of our deep space communication that can lead of our future space communication.